Climate change, agriculture, and adaptation options for Nicaragua - Rodriguez, Jorge; Thomas, Timothy S.; Cenacchi, Nicola; Rios, Ana R. (International Food Policy Research Institute, 2019)
This paper explores the impact of climate change on agriculture in Nicaragua using biophysical models and a bioeconomic model. It also examines differences in projections of key climate models. In Nicaragua’s case, the climate models strongly disagree in the direction of change in precipitation, with one model projecting large increases in rainfall and two projecting large decreases. This will keep policy makers from being able to invest in adapting to one type of outcome, though the report still makes recommendations for policies which will help farmers adapt to climate change. Most climate models show that rainfall will decline in the primera season (June–August), which only has a moderate amount of rainfall now. A decline in that season could result in a higher percentage of years with poor yields for maize and other crops. The bioeconomic model used in this report show that averaging across all growing seasons, sugarcane, coffee, maize, sorghum, and beans are expected to suffer negative shocks from climate change. And if the low-rainfall climate model proves to be correct, the losses will be much larger those projected here which rely on the median prediction from the climate models.